Optimizing the Performance of DPRD Members Through Competence and Work Ethic with Job Satisfaction as an Intervening Variable (Survey of the West Java Provincial DPRD) - Husin Husin; Yudi Wahyudin; Imas Komariyah (Pt. Anagata Sembagi Education, 2026)
This study aims to analyze the influence of competence and work ethics on the performance of members of the Regional House of Representatives (DPRD) of West Java Province, with job satisfaction as an intervening variable. The research method used is a survey with a quantitative approach. Data were collected through questionnaires distributed to members of the DPRD of West Java Province.The results of the study show that competence and work ethics have a significant influence on the performance of DPRD members. Additionally, job satisfaction is proven to be an intervening variable that strengthens the relationship between competence and work ethic on the performance of DPRD members. These findings indicate that the improvement of competence and work ethic not only has a direct impact on performance but also increases job satisfaction, which in turn positively contributes to the performance of DPRD members. This study provides practical implications for human resource management in governmental institutions, particularly in efforts to improve the performance of DPRD members through the enhancement of competence, work ethic, and job satisfaction.